Intra‐patient variability of the hair levels of pain medications in chronic migraine patients – a pilot study. Issue 6 (17th January 2019) - Ferrari, Anna; Rustichelli, Cecilia; Baraldi, Carlo; Vandelli, Daniele; Verri, Patrizia; Marchesi, Filippo; Licata, Manuela
Abstract: Monitoring of prescription pain medications is strongly recommended, considering their abuse liability. We used hair analysis for monitoring pain medications in 12 women with chronic migraine and drug overuse. Hair samples were collected at baseline and after 4 and 8 months and analyzed by liquid chromatography−electrospray tandem mass spectrometry (LC‐ESI‐MS/MS). Intra‐patient variability of the hair‐level‐to‐dose ratio was <20% in most cases. The hair analysis detected changes in the dose taken by the same patient over time, both occasionally and chronically. The agreement between the changes in hair drug levels and those of taken doses was excellent. Therefore, hair analysis appeared advantageous for long‐term monitoring of pain medications, which is otherwise difficult to determine in conventional matrices. In the same sample, multiple medications could be simultaneously determined, and with three samples, nine months of therapy were objectively documented. Abstract : Prescription drug abuse is epidemic in the Western world; therefore it is recommended to monitor patients taking analgesics and other psychoactive drugs. However, these medications are difficult to be determined in conventional matrices. We evaluated whether hair analysis was suitable to monitor pain medications prescribed to patients with chronic pain. Our results showed that, intra‐patient, the rate of incorporation of analgesic and psychoactive drugs in the keratin matrix was consistent over time, regardless of the dose taken.